Basic Futsal Game Technique Profile at MAS Muhammadiyah Palu (Grade X) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the profile of basic techniques of futsal games, especially in the aspects of passing and ball control, grade X students at MAS Muhammadiyah Palu. This study used a quantitative descriptive approach with a sample size of 12 students who participated in extracurricular futsal activities. The instrument used was a basic passing and ball control skills test of 10 items each, then classified into five categories using the average value and standard deviation. The results showed that in the aspect of ball control, 58% of students were in the very low category, and only 25% were classified as very high. Meanwhile, in the passing aspect, 50% of students were in the very low category, and only 17% were in the very high category. There were no students in the medium or high categories for both aspects. These findings indicate that the majority of students have not mastered the basic techniques of futsal optimally, and require a structured and systematic training program to improve their ability to control and pass the ball.